Manajemen Teaching Factory Dalam Membentuk Real Vocation Pada Program Keahlian Tata Busana Di SMKN 3 Malang - Erviana Erviana; Imron Arifin; Nurul Ulfatin; Erviana Erviana; Imron Arifin (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: The concept of teaching Factory Learning in vocational education (vocational high school) is one of the government's steps to prepare competent and ready to work graduates, as implemented in SMKN 3 Malang, especially in the fashion expertise program. The purpose of this research is to know: (1) a teaching factory profile, (2) teaching factoty planning, (3) organizing teaching factory, (4) implementing teaching factory, (5) teaching factory evaluation. This study used a qualitative approach with this type of case study research. Data is obtained through data collection, data reduction, data presentation, and data verification. The validity checks of data apply triangulation, member checking, and adequacy of reference material. Conclusion: (1) SMKN 3 Malang in cooperation with Sevencols to provide a real learning experience to the students in improving the competence and entrepreneurial spirit, the work program in relation to the learning and management of Three Can production unit, products in the form of goods and services, the result of improving the competence of students and graduates who are competent. (2) Planning includes goal setting, preparation of organisational structure, procurement of cooperation with industry, synchronization of curriculum and infrastructure, procurement of skilled educators resources. (3) Organizing includes the creation of an organizational structure with job descriptions. 4) The implementation of competency based learning & production is carried out according to the schedule and supported by the means & industry standard infrastructures, competency based learning teaches various vocational competencies and production activities while learning practices in production units related to entrepreneurship, customer service, order management and promotion. (5) Evaluation of product evaluation to produce products worth selling and evaluation of learners ability through level test and LSP test to produce competent learners. Abstrak: Konsep pembelajaran Teaching Factory dalam pendidikan SMK (Sekolah Menengah Kejuruan) menjadi salah satu langkah pemerintah untuk menyiapkan lulusan yang berkompetensi dan siap kerja, sebagaimana yang diterapkan di SMKN 3 Malang khususnya program keahlian Tata Busana. Tujuan penelitian ini untuk mengetahui: (1) profil Teaching Factory, (2) perencanaan Teaching Factory, (3) pengorganisasian Teaching Factory, (4) pelaksanaan Teaching Factory, (5) evaluasi Teaching Factory. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Data diperoleh melalui pengumpulan data, reduksi data, penyajian data, dan memverifikasi data. Pengecekan keabsahan data menerapkan triangulasi, pengecekan anggota, dan kecukupan bahan referensi. Simpulan: (1) SMKN 3 Malang bekerja sama dengan Sevencols untuk menghadirkan pengalaman belajar secara nyata pada peserta didik dalam meningkatkan kompetensi serta jiwa kewirausahaan, program kerja berkaitan dengan pembelajaran dan pengelolaan unit produksi Three Can, produk berupa barang dan jasa, hasilnya berupa peningkatan kompetensi peserta didik dan lulusan yang berkompeten. (2) Perencanaan meliputi penetapan tujuan, penyusunan struktur organisasi, pengadaan kerja sama dengan industri, sinkronisasi kurikulum dan sarana prasarana, pengadaan sumber tenaga pendidik terampil. (3) Pengorganisasian meliputi pembuatan struktur organisasi disertai job descriptions. 4) Pelaksanaan pembelajaran berbasis kompetensi & produksi dilaksanakan sesuai jadwal serta didukung dengan sarana & prasarana berstandar industri, pembelajaran berbasis kompetensi mengajarkan berbagai kompetensi kejuruan dan kegiatan produksi sedangkan pembelajaran praktik di unit produksi berkaitan dengan kewirausahaan, pelayanan pelanggan, pengelolaan pesanan dan promosi. (5) Evaluasi berupa evaluasi produk untuk menghasilkan produk layak jual dan evaluasi kemampuan peserta didik melalui uji level dan uji LSP menghasilkan peserta didik yang berkompeten.